Physical attractiveness and monetary success in German Bundesliga. (2nd January 2017) - Rosar, Ulrich; Hagenah, Jörg; Klein, Markus
Abstract : That attractive people are more successful has been proved for many areas of life in the past. However, the effects of the attractiveness of professional athletes have not been examined yet. This is surprising as it is comparatively simple to measure the actual performance of this group of people and to control their performance in statistical models. In the study, 438 professional football players were examined who played in the 18 teams of the German Bundesliga in 2007 and 2008. It was analyzed how their facial and bodily attractiveness influence their market value. Bodily attractiveness was operationalized using the Body Mass Index, facial attractiveness was measured using the Truth of Consensus Method. Statistical analysis shows that both facial and bodily attractiveness have considerable effects on a player's market value even if his actual performance is controlled.